The History of Contemporary Indonesian Muslim Groups and Muslim Media - Twediana budi hapsari (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2018)
Indonesia as the most populous Muslim country in the world is always interesting to be explored. Not only consist of more than 300 local ethnics, but also as the third most democratic country after India and USA. However, Indonesian Muslims are diverse into different groups, which started from the early 20s century, and also developed their own Muslim media channels. However, it seems that the political change in Indonesia has biggest influence to the growth of Muslim groups in Indonesia. Therefore, this article attempts to describe this influence into both Muslim groups and media from early 1900s to 2010.